2019
DOI: 10.17245/jdapm.2019.19.3.159
|View full text |Cite
|
Sign up to set email alerts
|

Painless injections–a possibility with low level laser therapy

Abstract: Background Dental procedures commonly involve the injection of local anesthetic agents, which causes apprehension in patients. The objective of dental practice is to provide painless treatment to the patient. The purpose of this study was to evaluate the effect of Low Level Laser Therapy (LLLT) in reducing the pain due to local anesthetic injection. Materials and Methods A prospective, split-mouth study was conducted on 25 patients. In Condition A, LLLT was administered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
43
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(45 citation statements)
references
References 27 publications
2
43
0
Order By: Relevance
“…Similarly, Tuk et al 13 evaluated pre‐injection analgesic effects of LLLT (wavelength—810 nm; continuous mode, output power—198 mW; energy—5.94 J) in patients undergoing third molar removal and reported that LLLT was not effective in decreasing the pain felt during the administration of the local anesthetic injections. On the contrary, Jagtap et al 14 (wavelength—660nm; output power—0.6 W; 3 min) and Ghabraei et al 15 (wavelength—980nm; contact mode, output power—0.3 W; 20 s; 15.62 J/cm 2 ; 0.384 cm 2 focal spot area; energy—6 J) concluded that LLLT before the injection of local anesthesia reduced injection pain in adults. There are many parameters that determine the effect of LLLT, and thus, the differences in these parameters make it challenging to compare across studies.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Similarly, Tuk et al 13 evaluated pre‐injection analgesic effects of LLLT (wavelength—810 nm; continuous mode, output power—198 mW; energy—5.94 J) in patients undergoing third molar removal and reported that LLLT was not effective in decreasing the pain felt during the administration of the local anesthetic injections. On the contrary, Jagtap et al 14 (wavelength—660nm; output power—0.6 W; 3 min) and Ghabraei et al 15 (wavelength—980nm; contact mode, output power—0.3 W; 20 s; 15.62 J/cm 2 ; 0.384 cm 2 focal spot area; energy—6 J) concluded that LLLT before the injection of local anesthesia reduced injection pain in adults. There are many parameters that determine the effect of LLLT, and thus, the differences in these parameters make it challenging to compare across studies.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, considering the pain-reducing effect of LLLT still being investigated, some of the studies combined topical anesthesia with LLLT, 12 whereas some did not use topical anesthesia but used the low-intensity laser therapy solely. 7,14 Therefore, there are contradictory results in the literature. Since the present study included paediatric patients, topical anesthesia and LLLT were used together.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations